Pengaruh Zeolit dan Pupuk Organik Terhadap pH, N-Total, Residu-P Tanah dan Hasil Tanaman Padi Sawah (Oryza sativa L.) Kultivar Ciherang Pada Fluventic Eutrudepts - Emma Trinurani Sofyan; Muhammad Farghan Fauzan (Fakultas Pertanian Universitas Padjadjaran, 2014)
The objective of this research was to find out the effect of zeolite and organic fertilizer on pH, total of N, P-residue, and yield of Ciherang cultivar’s rice (Oryza sativa L.) on Fluventic Eutrudepts. This research was conducted between May and August 2010 at the field station of soil and water management, soil science and land resources management department, Faculty of Agriculture, Padjadjaran University, in Jatinangor elevated 725 meters above the sea level. This research used Randomized Block Design with two factorial models. The first factor was zeolite dosage which consisted of three levels i.e: without zeolite, 150 kg.ha-1 and 300 kg.ha-1 zeolite. And the second factor was organic fertilizer consisted of three levels i.e: without organic fertilizer, 5 t.ha-1, 10 t.ha-1 with three replication, so that the total plots were 27. The result of this research showed that there was an interaction between zeolite and organic fertilizer on P-residue of soil, but there was no interaction on pH, total of N, potential of P and rice (Oryza sativa L.) yield. Zeolite application has a significant effect on soil’s total of N of 0,24 %, and organic fertilizer has a significant effect on rice yield of 5,48 kg ha-1.